Design Application System of B2G Sales Internal Management Using Waterfall Method - I Gusti Agung Made Yoga Mahaputra (International Journal of Engineering and Emerging Technology, 2021)
Technological developments in the era of globalization have triggered developments in various important sectors of the environment. The development of technology in the current economic sector is increasingly rapid where technology has been used in business development systems. PT Dwi Srikandi Nusantara, a medical device sales company, is now one of the providers in the sale of e-catalog procurement for the type of businees to government sales. But the problem arises because the company does not yet have a B2G sales management system and can be used as a monthly report. So from this research an application is designed that can be an internal B2G sales management application and can be used as a monthly report. The research was conducted using the waterfall method as a system development method designed. The research starts from the requirements stage by analyzing customer needs, then making a system design that is built, implementing the design into coding, and testing the functionalities of each part of the system. From the research that has been done, it is found that the results of the application system design have been successfully carried out and from the results of functional testing, the overall results of the system in the application are successfully functioning according to user needs.